Body Mass Index Changes at 1.5 and 3 Years of Age Affect Adult Body Composition - Chiharu Miyayama; Hiromichi Shoji; Yayoi Murano; Kanami Ito; Mizue Saita; Toshio Naito; Hiroshi Fukuda; Toshiaki Shimizu (Pediatric Reports)
Early childhood lays the foundation for many outcomes in later life. Recent studies suggest that early childhood development may contribute to lifestyle-related diseases such as obesity, type 2 diabetes, and cardiovascular disease in adulthood; however, there have been few investigations on this association among adults in Japan. Therefore, we examined the relationship between recent physical measurements in adults who underwent health checkups at our university and their physical measurements at birth and during infancy recorded in the Maternal and Child Health Handbook. The median age and body mass index (BMI) of the participants were 36 years and 20.4 kg/m2, respectively. BMI at the time of health checkup in adults did not correlate with physical measurements at birth, but it was found to be associated with BMI at 1.5 (regression coefficient (β) 0.53, p < 0.05) and 3 (β 0.7, p < 0.01) years of age. In addition, the waist-to-height ratio in adulthood was also associated with BMI at 1.5 (β 0.01, p < 0.05) and 3 (β 0.01, p < 0.05) years of age. These findings suggest that it is critical to provide appropriate guidance to children with high BMI and their parents during health checkups to prevent lifestyle-related disorders in adulthood.